Alterations in Arbuscular Mycorrhizal Community Along a Chronosequence of Teak (Tectona grandis) Plantations in Tropical Forests of China - Yu, Zhi; Liang, Kunnan; Wang, Xianbang; Huang, Guihua; Lin, Mingping; Zhou, Zaizhi; Chen, Yinglong (Frontiers in Microbiology, 2021)
Background and aims: Teak (Tectona grandis L.f.) is one of the most promising timber species in the tropical and subtropical areas in south China. Arbuscular mycorrhizal (AM) fungi play a crucial role in promoting plant growth, enhancing plant stress resistance and sustaining healthy ecosystem. However, little is known about mycorrhizal status in teak plantations. This study aims to characterize the dynamics of AM fungal communities in the rhizosphere of teak plantations at different ages. Methods: Fine roots and rhizosphere soils in teak plantations at varying ages (22, 35, 45 and 55 years old), and the adjacent native grassland without teak plantation (CK) were assessed for soil properties, root mycorrhizal colonization, and AM fungal communities using amplicon sequencing technology. Results: With the increase of stand ages, AM fungal colonization rates in teak fine root samples and spore density in the rhizosphere were increased linearly; catalase and ammonium nitrogen in the rhizosphere soil were also increased; soil organic carbon, total phosphorous (P), acid phosphatase, available potassium (AK) and available phosphorus (AP) were first increased and then declined at 55 years old stands. In total, 12 and 9 AM fungal genera were detected in the rhizosphere soil and in teak root samples, respectively. The OTUs data revealed that AM fungi presented in the rhizosphere soil and roots were mostly belonged to Glomus. In the rhizosphere soil, the relative abundance of Glomus was first increased and then declined, while Gigaspora and Scutellospora were declined, although the diversity and richness of AM fungi showed no significant variation with stand ages. In roots, the composition of AM fungal community and its diversity did not change with stand ages, whereas the richness was increased with the stand age. The monte carlo permutation test indicated that AK, nitrate nitrogen and C/P ratio largely explained the shift in the composition of AM fungal community in the rhizosphere soil. Conclusion: The results demonstrated that AM fungal communities in the rhizosphere soil and teak roots shifted across plantation ages. These changes were largely attributed to the age-induced variation in soil properties.